The Impact of Workload, Burnout, and Organizational Commitment on Cyberloafing Actions - Anindita, Maya Sri; Sitaniapessy, Arthur; Widokarti, Joko Rizkie (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2024)
This study analyzes the influence of workload, burnout, and organizational commitment on cyberloafing actions. The rapid advancement of technology has led to significant changes in work patterns. A negative effect of internet technology is the indication that internet usage has no relation to work-related interests (cyberloafing). Increasing workloads have caused burnout and impacted organizational commitment. The method used in this research is quantitative. The test results show that, of the three hypotheses tested, one hypothesis was not supported, namely the effect of workload on cyberloafing.